Answer:
10 for the empty box
Step-by-step explanation:
When your placing them on the graph the one on the left side is x axis (the horizontal line) and the one on the right is the y axis (the vertical line)
Hope this helps!
We are given the data ho equal to 704 feet and vo equal to 112 feet per second. We apply then kinematics equation: h = ho + vot - 1/2 gt2. Substituting to the given equation,
h = 704 + 112t - 1/2 * 32*t2when h is equal to zero,0 = 704 + 112t - 1/2 * 32*t2t is equal to 11 seconds
Step-by-step explanation:
since both objects and sides are similar, you can set each side equal, then you cross multiply, and do subtraction, then find x.
Square meters to square centimeters metric area units conversion factor 10000. To find out how many square centimeters in sq. meters, please use the converter below.
1 Sq. Meter = 10 000 Sq. Centimeters
Sq. meter is an area unit in metric system and used widely in measuring the small lands, floor plans etc. It equals to 10.7639104 sq. feet. The abbreviations are "m2" or "sq m".
Sq. centimeter is an area unit in metric system and defined as the area of a square whose sides are exactly one centimeter in length. It equals to 0.15500031 sq. inch. The abbreviations are "cm2" and "sq cm".
Please let me know if you need additional help in private messages.
Thanks,
-GeVontae The BRAINLY Team.
<h3>Answer: Choice B) </h3><h3>-6x - 2y = 12</h3>
===============================================
Explanation:
The x intercept is (-2,0) which is where the graph crosses the x axis.
The y intercept is (0,-6) which is where the graph crosses the y axis.
-----
Find the slope of the line through those two points
m = (y2-y1)/(x2-x1)
m = (-6-0)/(0-(-2))
m = (-6-0)/(0+2)
m = -6/2
m = -3
-----
The y intercept (0,-6) leads to b = -6
Both m = -3 and b = -6 plug into y = mx+b to get
y = mx+b
y = -3x+(-6)
y = -3x-6
-----
Now add 3x to both sides
y = -3x-6
y+3x = -3x-6+3x
3x+y = -6
-----
Lastly, multiply both sides by -2 so that the "-6" on the right hand side turns into "12" (each answer choice has 12 on the right hand side)
3x+y = -6
-2(3x+y) = -2(-6)
-2(3x)-2(y) = 12
-6x-2y = 12
which is what choice B shows.